2020
DOI: 10.1007/s12182-020-00516-z
|View full text |Cite
|
Sign up to set email alerts
|

Laponite: a promising nanomaterial to formulate high-performance water-based drilling fluids

Abstract: High-performance water-based drilling fluids (HPWBFs) are essential to wellbore stability in shale gas exploration and development. Laponite is a synthetic hectorite clay composed of disk-shaped nanoparticles. This paper analyzed the application potential of laponite in HPWBFs by evaluating its shale inhibition, plugging and lubrication performances. Shale inhibition performance was studied by linear swelling test and shale recovery test. Plugging performance was analyzed by nitrogen adsorption experiment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 56 publications
(72 reference statements)
2
19
0
Order By: Relevance
“… 89 Likewise, previous studies reported that the Bingham plastic model fits in a very good manner the experimental data of WBDFs using graphene nanoparticles and Laponite 2D layered nanoparticles as additives. 71 , 90 …”
Section: Rheology and Viscoelastic Propertiesmentioning
confidence: 99%
“… 89 Likewise, previous studies reported that the Bingham plastic model fits in a very good manner the experimental data of WBDFs using graphene nanoparticles and Laponite 2D layered nanoparticles as additives. 71 , 90 …”
Section: Rheology and Viscoelastic Propertiesmentioning
confidence: 99%
“…[66][67][68][69] Recently, a surfaceimproved asymmetric reaction was developed using in situ adsorbed L-proline (L-Pro) over LAPONITE® (Lap), 70 a synthetic layered magnesium silicate cation-exchanger clay. 71 The Michael addition of aldehydes to β-nitrostyrene occurred with exceptionally increased enantioselectivities compared to the use of L-Pro. Detailed studies indicated that the reaction takes place on the surface of the hybrid material; moreover, the performance of the primary amino acids (L-valine (L-Val), L-Phe, L-Trp) was also improved in the presence of Lap, which interestingly, provided the opposite enantiomer in excess compared to L-Pro.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with the gradual advancement of exploration and the development of low-porosity and low-permeability sandstone reservoirs, the study of the microscopic mechanism of formation damage by drilling fluid has received increasing attention in recent years. At present, the experimental methods for studying the damage to rocks caused by drilling fluid at the microscopic scale include thin-section observations [13,14], scanning electron microscope (SEM) observations [15,16], X-ray diffraction (XRD) [17], nuclear magnetic resonance (NMR) imaging [18], CT scanning [19], etc. The main idea of these methods is similar: first, obtaining rock samples (from drilling) before drilling fluid damage and rock samples (from core flooding experiments) after drilling fluid damage and then scanning or observing the rock samples before and after drilling fluid damage at the microscopic scale, and comparing the differences between them to determine the characteristics of formation damage.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of these methods is similar: first, obtaining rock samples (from drilling) before drilling fluid damage and rock samples (from core flooding experiments) after drilling fluid damage and then scanning or observing the rock samples before and after drilling fluid damage at the microscopic scale, and comparing the differences between them to determine the characteristics of formation damage. Among these methods, the advantage of both the thin-section and SEM observation methods is that high-resolution microscopic images can be obtained, which can characterize the formation damage caused by the solid particles from drilling fluid blocking the pores [13][14][15][16]. The advantage of the XRD method is that the influence of the composition and content of the solid particles in drilling fluid on the formation damage can be quantitatively analyzed [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation